Large-Cell Esophageal Neuroendocrine Tumor Leading to Hepatorenal Syndrome - Umar, Zaryab; Ilyas, Usman; Otusile, Ibironke; Landry, Ian (Curēus (Palo Alto, CA), 2022)
Neuroendocrine tumors are tumors that arise from the enterochromaffin cells in the neuroendocrine tissue found throughout the body, particularly the digestive tract, pancreas, and thymus. Neuroendocrine tumors of the esophagus are extremely rare and highly aggressive in nature. We present the case of a 55-year-old Hispanic male who initially presented to the emergency department with right-sided abdominal pain. Imaging revealed innumerable lesions occupying half of the liver parenchyma. Subsequent endoscopy with biopsy of the esophageal and liver lesions along with immunohistochemistry staining was suggestive of a large cell neuroendocrine tumor. He later presented with generalized weakness and right-sided abdominal pain with worsening hepatic and renal function. Over the course of the patient's stay in the hospital, his mental status progressively deteriorated. Given the deranged hepatic and renal function, chemotherapy could not be initiated. The patient's family decided against hemodialysis considering his poor prognosis and the patient expired on day 15 of admission. The case report highlights the aggressiveness of one of the rare esophageal malignancies. It is crucial to establish diagnosis at the earlier stages of the disease with prompt treatment in order to avoid serious complications such as hepatorenal syndrome, which resulted in rapid deterioration of our patient's clinical status. More research is necessary in order to establish guidelines to treat neuroendocrine tumors of the esophagus.